Breeding bird communities of the pine forests in the forest-steppe zone - A. Atemasov; T. Atemasova (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія)
The avifauna of pine forests in the North-East of Ukraine has been poorly studied. Analysis of bird communities showed that the avifaunal complexes of pine forests are poorer and have minimal similarity to those in deciduous forests. This study aimed to assess the species composition and densities of birds in the pine forest of various ages. Research was conducted on the National Park «Slobozhanskiy», located within the Krasnokutsk United Territorial Community of the Bogodukhiv District in the northwestern part of Kharkiv Region (Ukraine). Most of the park's forests are of artificial origin. Birds communities were studied in May 2023 in six forest types: pine forest less than 25 years old, pine forest 71-90 years old, pine forest 91-110 years old, pine forest over 110 years old, patches of oak stands and patches of birch stands. The point-count technique was used for bird sampling. Overall 60 point-count stations (10 in each forest type) were located using a forest map. The breeding avifauna was classified concerning nest location, according to the sites for searching food, and based upon migration patterns. We registered 39 breeding bird species during point counts; of them 3 were cavity excavators, 13 were secondary cavity users, 13 were tree and 3 were shrub foliage nesters and 6 were ground nesters. There were 7 trunk-foraging species, 15 canopy-foraging species, 3 shrub-foraging species, and 12 ground-foraging species. Eighteen species were long-distance migrants, 6 species were short-distance migrants, and 15 species were residents. The least number of species (16) was recorded in pine forests less than 25 years old. The number of species in other forest types varies slightly (23-25). The lowest total abundance was noted in pine forests less than 25 years old, and the highest in patches of oak stands. Total density differs between all types of forest, except for a couple of pine forests 91-110 years old – patches of birch stands. In pine forest less than 25 years old dominate European Robin (45.1%) and Common Chiffchaff (25.3%); in pine forest 71-90 years old – Wood Warbler (28.3%) and Common Chaffinch (20.4%); in pine forest 91-110 years old – Common Chaffinch (16.4%), Wood Warbler (12.9%), Collared Flycatcher (12.0%), and European Robin (10.9%); in pine forest over 110 years old – Common Chaffinch (18.7%), European Robin (15.0%), Great Tit (12.8%) and Collared Flycatcher (11.9%); in patches of oak stands – Collared Flycatcher (20.1%), Great Tit (19.3%) and Common Chaffinch (14.3%); and in patches of birch stands – Wood Warbler (20.6%), Collared Flycatcher (16.7%), European Robin (14.9%) and Common Chaffinch (13.3%). The most abundant birds in pine forests less than 25 years old were ground nesters (70.5%). In other age groups of the pine forest and the patches of birch stands, secondary cavity users and ground nesters co-dominated. In patches of oak stands secondary cavity users dominated (50.8%). In all types of forests, except for the pine forest less than 25 years old canopy gleaners dominated. Large-distance migrants were the most abundant birds in pine forests. except the pine forest less than 25 years old. and patches of birch stands. In the pine forests less than 25 years old short-distance migrants dominated (56.5%). Residents dominated in patches of oak stands (39.7%). We compared our results with those of other studies conducted in the region's pine forests since the mid-19th century.